Female Foeticide and Infanticide in India: An Analysis of Crimes against Girl Children - Mittal, Renu (Journal of Advanced Research in Humanities and Social Sciences; Vol 7 No 3 (2020): Journal of Advanced Research in Humanities and Social Science, 2021)
All over the world and in all societies violence against women exists in various forms. However, the recognition that elimination of gender-based violence is central to equality, development and peace is recent. In India, the landmark report on the status of women 1975 did not deal with this issue. In late seventies and eighties, the Indian women’s movement focused on the issues of dowry deaths, female foeticide, sati, rape and other forms of violence. In 1996 the world health assembly endorsed the fact that violence against women is a public health problem and female foeticide is one extreme manifestation of violence against women. How to cite this article:  Mittal R. Female Foeticide and Infanticide in India: An Analysis of Crimes against Girl Children. J Adv Res Humani Social Sci 2020; 7(3): 1-5. DOI: https://doi.org/10.24321/2349.2872.202003